Firocoxib on aqueous humor prostaglandin E 2 levels for controlling experimentally-induced breakdown of blood-aqueous barrier in healthy and Toxoplasma gondii -seropositive cats - Schroder,Deise Cristine (2016)
ABSTRACT: This study aimed to evaluate the effects of firocoxib for controlling experimentally-induced breakdown of the blood-aqueous barrier in healthy and Toxoplasma gondii -seropositive cats. Thirty two cats with no ocular abnormalities were used. Groups (n=8/each) were formed with healthy cats that received 5mg g-1 of oral firocoxib (FH) or no treatment (CH) on day 0; seropositive cats for anti -T. gondii specific immunoglobulin G (IgG) were grouped (n=8/each) and treated in a similar fashion (FT and CT). On day 1, cats of all groups received the same treatment protocol, and 1h later, aqueocentesis was performed under general anesthesia (M0). Following 1h, the same procedure was repeated (M1). Quantitation of aqueous humor total protein and prostaglandin E2 (PGE2) were determined. Aqueous samples of seropositive cats were tested for anti- T. gondii specific IgG. In M0, aqueous samples of CT showed a significantly higher concentration of PGE2 in comparison with other groups (P<0.05). In all groups, PGE2 concentration increased significantly from M0 to M1 (P=0.001). PGE2 values did not change significantly between groups in M1 (P=0.17). Anti- T. gondii specific IgG were reported only in samples of M1, and aqueous titers did not change significantly between FT and CT (P=0.11). Although we have observed that aqueous humor PGE2 levels were significantly higher in cats of CT group during M0, such increase was not able to break the blood-aqueous barrier and cause anterior uveitis. Firocoxib did not prevent intraocular inflammation after aqueocentesis, in healthy and toxoplasmosis-seropositive cats.